2021
DOI: 10.1038/s41598-021-03337-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenol-rich alternatives for Rosa x damascena Mill. Efficient phytochemical profiling using different extraction methods and colorimetric assays

Abstract: Damask rose is a well-established, abundant source of phytochemicals, as well as economically important essential oil—however, its cultivation is demanding and costly. In this paper, extracts from four raw plant materials—Salvia officinalis, Sambucus nigra, Matricaria chamomilla, Calendula officinalis, known to be rich in phenolic compounds, but also far easier to cultivate—were directly compared to those obtained from Rosa × damascena Mill. By combining diverse extraction methodologies (in a Soxhlet apparatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…Consistent with our find-ings, silymarin, an approved hepatoprotective drug, ameliorates APAP-provoked hepatic inflammation and subsequent liver injury [48]. The yield of ERS from dried rose buds and the contents of five representative compounds in ERS were similar to data published previously, suggesting the process of ERS preparation is reliable and stable [49,50]. Our results collectively suggested that ERS has the potential to alleviate APAP liver injury and support the application of ERS as a promising hepatoprotective reagent.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our find-ings, silymarin, an approved hepatoprotective drug, ameliorates APAP-provoked hepatic inflammation and subsequent liver injury [48]. The yield of ERS from dried rose buds and the contents of five representative compounds in ERS were similar to data published previously, suggesting the process of ERS preparation is reliable and stable [49,50]. Our results collectively suggested that ERS has the potential to alleviate APAP liver injury and support the application of ERS as a promising hepatoprotective reagent.…”
Section: Discussionsupporting
confidence: 91%
“…Recent research indicates that the phenolic compound composition in R. damascene extracts varies with the sample’s origin, showing an increasing trend from aqueous to hydro-methanolic extracts. These findings underscore the wide variability in polyphenols based on factors such as plant species, plant part, environmental conditions, and extraction methods [ 82 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result pinpoints the fact that R. damascena, with its diverse bioactive compounds like neral, geranial, phenyl ethyl, and phenolic compounds, exhibits inhibitory effects on microbial growth, targeting bacterial DNA gyrase and co-enzymes crucial for bacterial survival. Notably, phenolic compounds, including kaempferol and quercetin, showcase potential antimicrobial properties, making R. damascena a subject of interest for natural antimicrobial and anti-inflammatory agents [82,84,116]. Decoctions, essential oil, and absolute, methanol, and ethanol extracts of rose petals have exhibited antioxidant activity in different systems [117,118], as well as antimicrobial activity against S. aureus, S. typhimurium, B. cereus, C. albicans, P. aeruginosa, P. fluorescens, etc.…”
Section: The Antimicrobial and Antioxidant Capacity Of The Studied Ex...mentioning
confidence: 99%
“…Four methods including ultrasound-assisted extraction, reflux extraction, Soxhlet extraction, and marinated extraction for the extraction of anthocyanins from red rose petals were investigated and compared [ 135 ]. Another study also compared four extraction methods including Soxhlet extraction, ultrasound-assisted extraction, and microwave-assisted extraction, as well as supercritical CO2 extraction [ 136 ]. Although there are other extraction methods, steam distillation has been commonly used for essential oil extraction.…”
Section: Polymer and Materials Applicationmentioning
confidence: 99%